An Experimental Study of Torsional Properties of Polyvinylchloride - Rostam, Sarkawt; Hamakarim, Arazw; Xalid, Avan; Said, Pari; Muhammad, Kashab (Kurdistan Journal of Applied Research, 2017)
In this research, an experimental study has been performed to investigate the mechanical properties through torsion testing of polyvinylchloride (PVC) polymer specimens. For the purpose of the experimentation, specimens of PVC round bars have been prepared. Torsion testing machine apparatus of 200 Nm motor driven was used to evaluate the torsion properties of the tested bars. The apparatus provides four deformation speeds of 50°/min, 100°/min, 200°/min and 500 °/min. The tests conducted under different conditions in a room temperature and cooling of the samples and tested at different deformation speeds given by the torsion apparatus. Various tests produce the torsional moment- angle of rotation diagrams and thereafter both of torsional fracture resistance and shear modulus have been calculated. The results showed the effect of temperature change on the mechanical properties of PVC by making the material harder and can resist higher value of the applied torque where the range is from 2.9 N.m for the cooled sample to 2 N.m for the received samples tested at room temperature. Moreover the results showed an increase of shear modulus to 282 MPa for the cooled samples in compare to 140 MPa for as received samples. Finally the results provide a guideline for designers on how to use parts made of PVC in different applications where the range of both the maximum torque and failure torque with their mechanical properties of rigidity and torsional resistance were recorded.